2004
DOI: 10.1270/jsbbs.54.399
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of QTLs for Reproductive Development and Seed Quality Traits in Soybean using Recombinant Inbred Lines

Abstract: Soybean (Glycine max (L.) Merrill) is the most important leguminous crop in the world due to the high contents of protein and oil, and accumulation of various physiologically active substances. However, most of the genomic and economic traits in soybean are quantitative, controlled by multiple genes and easily affected by environmental conditions. Based on recombinant inbred lines (F 8 ), a genetic linkage map with 177 RFLP, 150 SSR, 28 AFLP markers and 5 phenotypic markers was constructed. The map covered a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
113
3
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(124 citation statements)
references
References 31 publications
7
113
3
1
Order By: Relevance
“…This phenomenon could be attributed to epistasis between the FT1 and FT3 loci. Statistical analysis showed that the recessive allele, ft1, reduced the effect of the FT3 allele (Yamanaka et al 2000;Watanabe et al 2004). Moreover, an allelism test between Harosoy and 6-22-ft3, both carrying the recessive ft1 (e1) allele, revealed a very small effect in the variation of flowering time (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon could be attributed to epistasis between the FT1 and FT3 loci. Statistical analysis showed that the recessive allele, ft1, reduced the effect of the FT3 allele (Yamanaka et al 2000;Watanabe et al 2004). Moreover, an allelism test between Harosoy and 6-22-ft3, both carrying the recessive ft1 (e1) allele, revealed a very small effect in the variation of flowering time (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, the E1, E3, and E4 loci have been suggested to be related to photoperiod sensitivity under various light conditions (Saidon et al 1989;Cober et al 1996b;Abe et al 2003). In previous studies, using the same populations as in this study, three flowering-time quantitative trait loci (QTL)-FT1, FT2, and FT3 loci-were identified and considered to be identical with the maturity loci E1, E2, and E3, respectively (Yamanaka et al 2001;Watanabe et al 2004). Although many loci related to soybean flowering and maturity have been identified, and some candidate genes were recognized using near isogenic lines (NILs) (Tasma and Shoemaker 2003), most of the genes responsible for these loci have not yet been isolated except for the E4 gene.…”
mentioning
confidence: 80%
“…None of the classical major genes controlling flowering and maturing times that have been mapped so far is located in LG O. Many QTL influencing the flowering and maturing times have been allocated to various LGs (Keim et al 1990;Mansur et al 1993;Lee et al 1996;Orf et al 1999;Tasma et al 2001;Yamanaka et al 2001;Chapman et al 2003;Watanabe et al 2004;Zhang et al 2004;Funatsuki et al 2005;Liu et al 2007). However, only a maturitycontrolling QTL has been located in LG O (Zhang et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The recessive alleles of the E2 (FT2) locus were perhaps unable to suppress GmFT2a expression and resulted in the early flowering phenotype. There are strong interaction among the effects of E1 (FT1) and E2 (FT2), E1 (FT1) and E3 (FT3) (Yamanaka et al 2000;Watanabe et al 2004). The e3e3 recessive homozygote can initiate flowering under R-enriched LD, but the e3e3 genotype is necessary for plants with e4 mutant allele to flower under FR-enriched LD.…”
Section: Putative Pathway Of Flowering Time In Soybeanmentioning
confidence: 97%
“…3). The FT1, FT2 and FT3 were considered to correspond to E1, E2, E3, respectively, based on their map positions (Yamanaka et al, 2001;Watanabe et al, 2004). The lateflowering alleles FT1, FT2 and FT3 are partially dominant over the early-flowering alleles, ft1, ft2 and ft3, respectively.…”
Section: Positional Cloning Of the Responsible Genes For The E1 E2 Amentioning
confidence: 99%